2009
DOI: 10.1159/000201000
|View full text |Cite
|
Sign up to set email alerts
|

Self-Evaluation of Voice as a Treatment Outcome Measure

Abstract: This study addressed two self-evaluation questionnaires in investigating the effects of voice hygiene lecture (VHL, 3 h) and additional voice training (VT) or Voice Massage™ (VM; both 5 h) in 90 female teachers. The subjects assessed their voice quality, ease of phonation and tiredness of throat before and after a working day at the beginning and end of the school term using a visual analogue scale (VAS) (Questionnaire 1). At the end of the term, the degree of positive influence of the interventions was report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
1
16
0
3
Order By: Relevance
“…The generally very positive experience reported after VM may reflect the fact that the participants of the VM group received personal attention from the therapist, which is prone to build positive interaction and confidentiality typically related to massage treatment [37] . In line with the present results, an earlier study [25] reported many positive sensations after VM, while no significant acoustic or perceptual effects were found. One reason may be that the type of change in acoustic or perceptual parameters that can be regarded as positive are prone to differ depending on the starting point (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The generally very positive experience reported after VM may reflect the fact that the participants of the VM group received personal attention from the therapist, which is prone to build positive interaction and confidentiality typically related to massage treatment [37] . In line with the present results, an earlier study [25] reported many positive sensations after VM, while no significant acoustic or perceptual effects were found. One reason may be that the type of change in acoustic or perceptual parameters that can be regarded as positive are prone to differ depending on the starting point (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…[23] . Some results for some of the same subjects, but with a different focus, have also been reported [23][24][25] . The questionnaire collected background variables like age, health (allergies, reflux etc.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…As a result of the initial search, 677 studies were identified, among which five (5,9,(13)(14)(15) fulfilled the inclusion criteria and were considered relevant for the sample of this work. Four more articles (3,4,16,17) , found in the references of the studies selected for the reading of the full text, were added as additional references.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, voice training exercises increase the blood flow and improve breathing, allowing the increase of muscle contractions and elasticity (8) . Several studies have shown positive effects of voice therapy and training in parameters assessed by acoustic and auditory-perceptual analyses in terms of decreased perturbation (jitter and shimmer), increased signal-to-noise ratio and a better vocal quality (9) . However, few prevention programs are designed for teachers and future teachers (7) .…”
Section: Introductionmentioning
confidence: 99%